Main Developmental Changes During Middle Childhood: The Role of Peers and School - Rzechowska, Ewa (Social and Personality Development in Childhood, 2025)
Middle childhood (6-11 years) is a complex period in human life in which children become pupils, having attained school maturity and readiness for reading and writing.The younger school-age period is characterised by children’s increasing awareness, control and purposefulness of attention, perception, memory and learning processes. Concrete operational thinking that children become capable of around 6 to 7 years of age makes it possible for them to reverse operations and decentrate. Both of these abilities are important for their social functioning, as they allow them to take others’ perspectives and understand that their states and expectations are different from those of other people. The changes are associated with the development of children’s identities and the formation and enhancement of interpersonal relations.In middle childhood, children’s sexual energy sublimates into explorations accompanied by defence mechanisms that, at this stage of development, play a positive role (Freud’s latency period). They also learn to be productive and accept others’ judgments on their performance (Erikson’s industry vs. inferiority). By comparing their own and others’ expectations, achievements, states and experiences, they start building their self-image; others’ opinions become a basis for them to develop self-concept, self-esteem and self-efficacy. Their ability to take a wider perspective on things is reflected in their moral judgments, which they make considering external expectations or social norms.In the early school years, children transition from a life focused on the family to a life concerned with peer relationships and school and develop a strong need to be part of a group. A special type of peer relationship is friendship, which can manifest itself in various forms.School is the second developmental environment for children after the family home, in which the quality of teacher-pupil relationships, informal class structure and procedures enabling a supportive environment are important. Among the various problems faced by school children, emotional and behavioural disorders and learning disabilities are the most frequent. The creation of a safe and stimulating educational environment requires procedures protecting children from bullying and supporting talented pupils.Keywords: middle childhood, school maturity, concrete operational thinking, identity development, peers, friendship, emotional and behavioural disorders, learning disabilities, peer bullying